2008
DOI: 10.2337/dc07-1528
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Retinal Vascular Caliber With Diabetes and Retinopathy

Abstract: OBJECTIVE -To examine the relationship of retinal vascular caliber with diabetes, glycemia, and diabetic retinopathy.RESEARCH DESIGN AND METHODS -Population-based study using data from the Multi-Ethnic Study of Atherosclerosis (MESA), comprising 5,976 individuals (whites, blacks, Hispanics, and Chinese) residing in six U.S. communities who were free of clinical cardiovascular disease at baseline. Retinal vascular caliber was measured from digital retinal photographs.RESULTS -There were 4,585 individuals with n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

14
161
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 195 publications
(176 citation statements)
references
References 24 publications
(27 reference statements)
14
161
1
Order By: Relevance
“…20 Our study now clearly shows that in Asian Malays, as in white population, wider retinal arterioles are associated with diabetes. The association of wider retinal venules with diabetic retinopathy signs in our study is also consistent with clinical experience, as well as with findings from white population from BMES, 10 AusDiab, 8 MESA, 7 and Wisconsin Epidemiological Study of Diabetic Retinopathy (WESDR). 6,9 The mechanisms underlying wider retinal arterioles with diabetes are uncertain, but multiple aetiologies have been suggested, including impaired autoreguation of small vessels caused by hyperglycaemia and hypoxia.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…20 Our study now clearly shows that in Asian Malays, as in white population, wider retinal arterioles are associated with diabetes. The association of wider retinal venules with diabetic retinopathy signs in our study is also consistent with clinical experience, as well as with findings from white population from BMES, 10 AusDiab, 8 MESA, 7 and Wisconsin Epidemiological Study of Diabetic Retinopathy (WESDR). 6,9 The mechanisms underlying wider retinal arterioles with diabetes are uncertain, but multiple aetiologies have been suggested, including impaired autoreguation of small vessels caused by hyperglycaemia and hypoxia.…”
Section: Discussionsupporting
confidence: 91%
“…However, due to the small number of Asian participants, such an observation would need confirmation by other studies. 7 We have now confirm that the effect of diabetes and diabetic retinopathy on the retinal vascular calibre in our Asian population are similar to that previously shown in white/Caucasian populations from MESA, 7 BMES, 10 and AusDiab 8 studies. Similarly, we have also previously shown that the effects of blood pressure on the retinal vascular calibre in this population are similar to that observed in white populations.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Recent observations from the Multi-Ethnic Study of Atherosclerosis (MESA) in the US showed wider adjusted central retinal artery equivalents in African American participants compared with White American participants across categories of normoglycaemia, impaired fasting glucose and diabetes, although a statistical comparison of this difference between ethnic groups were not reported. Interestingly, in MESA there was attenuation of the trend for wider retinal arterioles with increasing dysglycaemia in African Americans compared with White Americans [42].…”
Section: Discussionmentioning
confidence: 89%
“…Several reasons for this have been suggested including differences in BP, duration or onset of diabetes, and glycaemic control. A previous large population-based study [41] also reported that increased duration of diabetes was associated with arteriolar widening assessed using AVR and more recent observations from the Multi-Ethnic Study of Atherosclerosis (MESA) also showed significantly wider retinal arterioles in people with diabetes, despite high blood pressures [42]. Our observations also indicate that differences in duration of diabetes may at least partially explain ethnic differences in arteriolar narrowing in diabetes, however although differences arteriolar narrowing were no longer statistically significant after adjustment for duration of diabetes they remained substantial and we cannot exclude that other factors contribute to inter-ethnic differences in retinal arteriolar narrowing.…”
Section: Discussionmentioning
confidence: 90%